State and nature studies in ancient and medieval philosophy - Adamson, Peter; Brouwer, René; Brüllmann, Philipp; Horn, Christoph; Humfress, Caroline; Karamanolis, George; Keyt, David; Lienemann, Béatrice; Miller, Fred D.; Noble, Christopher Isaac; O'Keefe, Tim; Pelletier, Jenny; et al. (De Gruyter, 2021)
A much-maligned feature of ancient and medieval political thought is its tendency to appeal to nature to establish norms for human communities. From Aristotle's claim that humans are "political animals" to Aquinas' invocation of "natural law," it may seem that pre-modern philosophers were all too ready to assume that whatever is natural is good, and that just political arrangements must somehow be natural. The papers in this collection show that this assumption is, at best, too crude. From very early, for instance in the ancient sophists' contrast between nomos and physis, there was recognition that political arrangements may be precisely artificial, not natural, and it may be questioned whether even such supposed naturalists as Aristotle in fact adopt the quick inference from "natural" to "good." The papers in this volume trace the complex interrelations between nature and such concepts as law, legitimacy, and justice, covering a wide historical range stretching from Plato and the Sophists to Aristotle, Hellenistic philosophy, Cicero, the Neoplatonists Plotinus and Porphyry, ancient Christian thinkers, and philosophers of both the Islamic and Christian Middle Ages.